Flame retardant for coating and preparation method thereof
By using zirconium tungstate as the core layer and superbranched silicone and hydroxypropyl methylcellulose composite sol as the shell layer in the flame retardant for coatings, the problem of cracking of the coating at high temperature is solved, and the flame retardant performance and compatibility are improved.
Patent Information
- Application Number
- CN202411299361.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing flame retardants for coatings are prone to cracking under high temperature conditions, affecting the flame retardant effect and overall performance, and at the same time, there are poor compatibility and environmental protection problems.
The flame retardant for coatings using a core-shell structure is used. The core layer is composed of zirconium tungstate. The shell layer is obtained by composite sol of hyperbranched silicone and hydroxypropyl methylcellulose. The zirconium tungstate core layer provides good compatibility between the rigid core structure and the shell layer to avoid coating cracking.
The flame retardant performance and compatibility of the flame retardant for coatings is improved, effectively avoiding the problem of the coating cracking at high temperatures, and at the same time enhancing the mechanical strength and dimensional stability of the coating.
Smart Images

Figure BDA0005047156340000071 
Figure BDA0005047156340000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, in particular to a flame retardant for coatings and a preparation method thereof. Background Art
[0002] Flame retardants for coatings are an important type of additive used to improve the fire resistance of coating materials. With the development of modern industry and construction, people's requirements for safety, especially in public places, transportation and home decoration, are constantly increasing. Coatings not only need to provide aesthetic effects, but also need to have certain fire retardant properties to reduce fire risks and delay the spread of fire.
[0003] The mechanism of action of flame retardants for coatings includes physical isolation, endothermic reaction, gas inhibition and carbonization. Specifically, physical isolation means that the coating formed by the flame retardant can block oxygen from reaching the surface of the fuel; endothermic reaction means that some flame retardants absorb surrounding heat when heated, reducing the flame temperature; gas inhibition means that the non-combustible gas produced by the decomposition of flame retardants can dilute the oxygen concentration; and carbonization means that the intumescent flame retardant forms a porous carbon layer when heated, effectively isolating heat and oxygen. According to different chemical compositions, flame retardants are mainly divided into inorganic flame retardants, organic flame retardants, nano flame retardants and bio-based flame retardants.
[0004] Although some flame retardants on the market can improve the flame retardancy of coatings, they are prone to cracking of the coating under high temperature conditions, thus affecting the flame retardant effect and the overall performance of the coating. In addition, flame retardants for coatings also have technical defects such as poor compatibility, high temperature cracking, and environmental issues.
[0005] In view of these problems, the present invention aims to provide a flame retardant for coatings, which has good flame retardant properties, good compatibility with coatings, and can effectively avoid the problem of cracking of the coating at high temperatures when the flame retardant is used. Summary of the invention
[0006] In order to solve the existing technical problems, the present invention provides a flame retardant for coatings. The structure of the flame retardant for coatings is a core-shell structure. The core-shell structure includes a zirconium tungstate core layer and a flame retardant shell layer from the inside to the outside; the flame retardant shell layer is obtained by compounding a hyperbranched siloxane and a hydroxypropyl methylcellulose composite sol.
[0007] Furthermore, the zirconium tungstate core layer is obtained by sequentially mixing a zirconium source, a tungsten source and deionized water, and then sequentially adding a flocculant and an acid solution, and performing reflux, standing, filtering, washing, drying, grinding and heat treatment.
[0008] Furthermore, the hyperbranched siloxane is obtained by a mixed reaction of N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water;
[0009] Furthermore, the hydroxypropyl methylcellulose composite sol is obtained by sequentially adding acetic acid to chitosan, hydroxypropyl methylcellulose, and guar gum, and then adding graphene oxide and mixing.
[0010] The present invention also provides a method for preparing a flame retardant for coatings, comprising the following preparation steps:
[0011] (1) A zirconium source and deionized water are mixed in a mass ratio of 1:2 to 6, and stirred at a speed of 200 to 300 rpm to dissolve, and then a tungsten source is added, and stirring is continued for 30 to 60 minutes to obtain a primary mixed solution. At this time, the molar ratio of tetravalent zirconium ions and hexavalent tungsten ions contained in the primary mixed solution is 1:2. Then, 0.01 to 0.02 mass of polyvinyl pyrrolidone of zirconyl nitrate is added and stirring is continued for 10 hours. A 68% nitric acid solution is added to obtain a secondary mixed solution, and the mass fraction of nitric acid in the secondary solution is 3 to 15%. Then, reflux for 48 hours and stand for 21 days, filter, wash, dry, grind through a 100 to 200 mesh sieve, and heat treat at 610°C for 5 hours to obtain a zirconium tungstate core layer;
[0012] (2) ultrasonically dispersing the zirconium tungstate core layer obtained in step (1) in methanol with a volume of 30 to 50 times its mass for 20 to 40 minutes to obtain a zirconium tungstate core layer suspension; then dripping a mixture of hydroxypropyl methylcellulose composite sol and a methanol solution of hyperbranched siloxane into the zirconium tungstate core layer suspension, stirring continuously at a speed of 1200 to 1600 rpm during the dripping process, continuing to stir overnight after the dripping is completed, then filtering, rinsing repeatedly with deionized water and ethanol for 2 to 4 times in sequence, and then performing vacuum freeze drying to obtain a flame retardant for coatings.
[0013] Furthermore, the zirconium source includes zirconium oxynitrate; and the tungsten source includes ammonium tungstate.
[0014] Furthermore, the preparation method of the hydroxypropyl methylcellulose composite sol is as follows: chitosan, hydroxypropyl methylcellulose, and guar gum are sequentially added to a 5wt% acetic acid solution and stirred for 30 minutes, and then a 2mg / L graphene oxide solution is added, and the mixture is swelled at 60°C for 3 to 4 hours to obtain a hydroxypropyl methylcellulose composite sol.
[0015] Furthermore, in the hydroxypropyl methylcellulose composite sol, the content of chitosan is 0.75wt%, the content of hydroxypropyl methylcellulose is 2.5wt%, the content of guar gum is 0.1-0.2wt%, the content of graphene oxide is 0.2-0.4wt%, and the content of acetic acid is 0.5wt%.
[0016] Furthermore, the methanol solution of the hyperbranched siloxane is obtained by dissolving the hyperbranched siloxane in a methanol solution 8 to 10 times its mass; the hyperbranched siloxane is obtained by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water in a molar ratio of 1:1.2 to 1.4, then heating and stirring at 60°C for 8 hours, preparing a viscous liquid under the autocatalysis of amino groups, and then vacuum drying at 60°C.
[0017] Furthermore, the mass ratio of the hyperbranched siloxane methanol solution to the hydroxypropyl methylcellulose composite sol is 1:1-2; and the mass ratio of the hyperbranched siloxane to the zirconium tungstate core layer in the flame retardant for coating is 1-2:1.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The structure of the flame retardant for coatings of the present invention is a core-shell structure, and the core-shell structure comprises a zirconium tungstate core layer and a flame retardant shell layer from the inside to the outside; the flame retardant shell layer is obtained by compounding a hyperbranched siloxane and a hydroxypropyl methylcellulose composite sol; the zirconium tungstate core layer is obtained by sequentially mixing and stirring a zirconium source, a tungsten source and deionized water, and then sequentially adding a flocculant and an acid solution for reflux, standing, filtering, washing, drying, grinding and heat treatment; the hydroxypropyl methylcellulose composite sol is obtained by sequentially adding acetic acid to chitosan, hydroxypropyl methylcellulose and guar gum, and then adding graphene oxide for mixing; the flame retardant for coatings prepared by the present invention has good flame retardancy and good compatibility with coatings, and can effectively avoid the problem of cracking of the coating at high temperature caused by the use of the flame retardant.
[0020] The present invention adopts zirconium tungstate as the core layer of the flame retardant for coatings. Through this design, zirconium tungstate provides a rigid core structure for the flame retardant for coatings, enhances dimensional stability and improves overall mechanical strength. The good interface bonding between zirconium tungstate and the shell material helps to effectively transfer stress and control the morphology of the shell material. During the combustion process, the volume of the zirconium tungstate core layer decreases when heated, which can compensate for the problem of coating rupture caused by the volume expansion of the shell material after thermal expansion, thereby ensuring the integrity and flame retardant performance of the coating used by the flame retardant; and when the temperature reaches 700°C, the zirconium tungstate decomposes to obtain tungsten oxide and zirconium oxide with flame retardant properties.
[0021] The invention adopts chitosan, guar gum, hydroxypropyl methylcellulose and graphene oxide to prepare hydroxypropyl methylcellulose composite sol. Chitosan, as a natural polymer, has good water retention and moisture absorption capacity, and provides the required viscosity and stability for the gel. The viscosity and performance of the gel can be further adjusted by selecting chitosan with a high degree of deacetylation. Due to its temperature-sensitive characteristics, the gelation temperature of hydroxypropyl methylcellulose can be adjusted according to factors such as substitution degree and molecular weight, so that the gel can show different viscosity characteristics at a specific temperature. Guar gum increases the viscosity and viscoelasticity of the gel and retains moisture. Graphene oxide has good flame retardant properties and can form a dense protective film to effectively prevent heat transfer and inhibit the combustion process, thereby enhancing the flame retardant effect of the gel. When burning at high temperature, the hydroxypropyl methylcellulose composite sol expands after reaching a phase transition temperature of 67°C, and the expanded graphene oxide fills the gaps in the surface layer of the composite sol to form a dense carbon layer, which can isolate the transfer of oxygen and heat to the unburned area and slow down the combustion speed, thereby improving the flame retardant property of the hydroxypropyl methylcellulose composite sol.
[0022] The hyperbranched siloxane of the present invention has good compatibility with the hydroxypropyl methylcellulose composite sol and the zirconium tungstate core layer, so that the interface of the flame retardant shell layer and the zirconium tungstate core layer can be well combined together, and the zirconium tungstate core layer provides a rigid core structure for the shell layer, thereby enhancing the dimensional stability of the flame retardant for coatings and improving the overall mechanical strength. The flame retardant shell layer is prepared by compounding the hyperbranched siloxane with the hydroxypropyl methylcellulose composite sol, and the hydroxypropyl methylcellulose composite sol can penetrate into the cavity of the hyperbranched siloxane and be compounded with it, so that the flame retardant shell layer can be firmly attached to the zirconium tungstate core layer. When the flame retardant is used, the hydroxypropyl methylcellulose composite sol in the flame retardant shell layer can well combine the flame retardant for coatings with the coating, thereby ensuring the mechanical properties of the coating. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.
[0024] Some raw material information of the examples and comparative examples of the present invention are as follows:
[0025] The apparent viscosity of hydroxypropyl methylcellulose is 15000 mPa·s;
[0026] The guar gum used is food grade model HV-90 produced by Yanxin Minerals Co., Ltd.;
[0027] N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was obtained from Hubei Jianghan New Materials Co., Ltd.;
[0028] Example 1
[0029] A method for preparing a flame retardant for coatings, the preparation steps are as follows:
[0030] (1) A zirconium source and deionized water were mixed in a mass ratio of 1:2, stirred and dissolved at a speed of 20 rpm, and then a tungsten source was added and stirred for 30 minutes to obtain a primary mixed solution. At this time, the molar ratio of tetravalent zirconium ions and hexavalent tungsten ions contained in the primary mixed solution was 1:2. Then, 0.01 mass of polyvinyl pyrrolidone of zirconyl nitrate was added and stirred for 10 hours. A 68% nitric acid solution was added to obtain a secondary mixed solution. The mass fraction of nitric acid in the secondary solution was 3%. Then, the solution was refluxed for 48 hours and allowed to stand for 21 days. After filtering, washing, drying, grinding, and passing through a 100-mesh sieve, the solution was heat treated at 610°C for 5 hours to obtain a zirconium tungstate core layer.
[0031] (2) ultrasonically dispersing the zirconium tungstate core layer obtained in step (1) in methanol with a volume of 30 times its mass for 20 minutes to obtain a zirconium tungstate core layer suspension; then dropping a mixture of hydroxypropyl methylcellulose composite sol and a methanol solution of hyperbranched siloxane into the zirconium tungstate core layer suspension, stirring continuously at a speed of 1200 rpm during the dropping process, continuing to stir overnight after the dropping is completed, then filtering, rinsing repeatedly with deionized water and ethanol twice in sequence, and then performing vacuum freeze drying to obtain a flame retardant for coatings.
[0032] Furthermore, the zirconium source includes zirconium oxynitrate; and the tungsten source includes ammonium tungstate.
[0033] Furthermore, the preparation method of the hydroxypropyl methylcellulose composite sol is as follows: chitosan, hydroxypropyl methylcellulose, and guar gum are sequentially added to a 5wt% acetic acid solution and stirred for 30 minutes, and then a 2mg / L graphene oxide solution is added and swelled at 60°C for 3 hours to obtain a hydroxypropyl methylcellulose composite sol.
[0034] Furthermore, in the hydroxypropyl methylcellulose composite sol, the content of chitosan is 0.75wt%, the content of hydroxypropyl methylcellulose is 2.5wt%, the content of guar gum is 0.1wt%, the content of graphene oxide is 0.2wt%, and the content of acetic acid is 0.5wt%.
[0035] Furthermore, the methanol solution of the hyperbranched siloxane is obtained by dissolving the hyperbranched siloxane in a methanol solution 8 to 10 times its mass; the hyperbranched siloxane is obtained by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water in a molar ratio of 1:1.2, then heating and stirring at 60°C for 8 hours, preparing a viscous liquid under the autocatalysis of amino groups, and then vacuum drying at 60°C.
[0036] Furthermore, the mass ratio of the hyperbranched siloxane methanol solution to the hydroxypropyl methylcellulose composite sol is 1:1; and the mass ratio of the hyperbranched siloxane to the zirconium tungstate core layer in the flame retardant for coating is 1:1.
[0037] Example 2
[0038] A method for preparing a flame retardant for coatings, the preparation steps are as follows:
[0039] (1) A zirconium source and deionized water were mixed in a mass ratio of 1:4, stirred and dissolved at a speed of 250 rpm, and then a tungsten source was added and stirred for 40 minutes to obtain a primary mixed solution. At this time, the molar ratio of tetravalent zirconium ions and hexavalent tungsten ions contained in the primary mixed solution was 1:2. Then, 0.015 mass of polyvinyl pyrrolidone of zirconyl nitrate was added and stirred for 10 hours. A 68% nitric acid solution was added to obtain a secondary mixed solution. The mass fraction of nitric acid in the secondary solution was 9%. Then, the solution was refluxed for 48 hours and allowed to stand for 21 days. After filtering, washing, drying, grinding, and passing through a 200-mesh sieve, the solution was heat treated at 610°C for 5 hours to obtain a zirconium tungstate core layer.
[0040] (2) ultrasonically dispersing the zirconium tungstate core layer obtained in step (1) in methanol with a volume of 40 times its mass for 30 minutes to obtain a zirconium tungstate core layer suspension; then dropping a mixture of hydroxypropyl methylcellulose composite sol and a methanol solution of hyperbranched siloxane into the zirconium tungstate core layer suspension, stirring continuously at a speed of 1400 rpm during the dropping process, continuing to stir overnight after the dropping is completed, then filtering, rinsing repeatedly with deionized water and ethanol three times in sequence, and then performing vacuum freeze drying to obtain a flame retardant for coatings.
[0041] Furthermore, the zirconium source includes zirconium oxynitrate; and the tungsten source includes ammonium tungstate.
[0042] Furthermore, the preparation method of the hydroxypropyl methylcellulose composite sol is as follows: chitosan, hydroxypropyl methylcellulose, and guar gum are sequentially added to a 5wt% acetic acid solution and stirred for 30 minutes, and then a 2mg / L graphene oxide solution is added and swelled at 60°C for 3.5 hours to obtain a hydroxypropyl methylcellulose composite sol.
[0043] Furthermore, in the hydroxypropyl methylcellulose composite sol, the content of chitosan is 0.75wt%, the content of hydroxypropyl methylcellulose is 2.5wt%, the content of guar gum is 0.15wt%, the content of graphene oxide is 0.3wt%, and the content of acetic acid is 0.5wt%.
[0044] Furthermore, the methanol solution of the hyperbranched siloxane is obtained by dissolving the hyperbranched siloxane in a methanol solution 8 to 10 times its mass; the hyperbranched siloxane is obtained by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water in a molar ratio of 1:1.3, then heating and stirring at 60°C for 8 hours, preparing a viscous liquid under the autocatalysis of amino groups, and then vacuum drying at 60°C.
[0045] Furthermore, the mass ratio of the hyperbranched siloxane methanol solution to the hydroxypropyl methylcellulose composite sol is 1:1.5; and the mass ratio of the hyperbranched siloxane to the zirconium tungstate core layer in the flame retardant for coating is 1.5:1.
[0046] Example 3
[0047] A method for preparing a flame retardant for coatings, the preparation steps are as follows:
[0048] (1) A zirconium source and deionized water were mixed in a mass ratio of 1:6, stirred and dissolved at a speed of 300 rpm, and then a tungsten source was added and stirred for 60 minutes to obtain a primary mixed solution. At this time, the molar ratio of tetravalent zirconium ions and hexavalent tungsten ions contained in the primary mixed solution was 1:2. Then, 0.02 mass of polyvinyl pyrrolidone of zirconyl nitrate was added and stirred for 10 hours. A 68% nitric acid solution was added to obtain a secondary mixed solution. The mass fraction of nitric acid in the secondary solution was 15%. Then, the solution was refluxed for 48 hours and allowed to stand for 21 days. After filtering, washing, drying, grinding, and passing through a 200-mesh sieve, the solution was heat treated at 610°C for 5 hours to obtain a zirconium tungstate core layer.
[0049] (2) ultrasonically dispersing the zirconium tungstate core layer obtained in step (1) in methanol with a volume of 50 times its mass for 40 minutes to obtain a zirconium tungstate core layer suspension; then dropping a mixture of hydroxypropyl methylcellulose composite sol and a methanol solution of hyperbranched siloxane into the zirconium tungstate core layer suspension, stirring continuously at a speed of 1600 rpm during the dropping process, continuing to stir overnight after the dropping is completed, then filtering, rinsing repeatedly with deionized water and ethanol for 4 times in sequence, and then performing vacuum freeze drying to obtain a flame retardant for coatings.
[0050] Furthermore, the zirconium source includes zirconium oxynitrate; and the tungsten source includes ammonium tungstate.
[0051] Furthermore, the preparation method of the hydroxypropyl methylcellulose composite sol is as follows: chitosan, hydroxypropyl methylcellulose, and guar gum are sequentially added to a 5wt% acetic acid solution and stirred for 30 minutes, and then a 2mg / L graphene oxide solution is added, and the mixture is swelled at 60°C for 4 hours to obtain a hydroxypropyl methylcellulose composite sol.
[0052] Furthermore, in the hydroxypropyl methylcellulose composite sol, the content of chitosan is 0.75wt%, the content of hydroxypropyl methylcellulose is 2.5wt%, the content of guar gum is 0.2wt%, the content of graphene oxide is 0.4wt%, and the content of acetic acid is 0.5wt%.
[0053] Furthermore, the methanol solution of the hyperbranched siloxane is obtained by dissolving the hyperbranched siloxane in a methanol solution 8 to 10 times its mass; the hyperbranched siloxane is obtained by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water in a molar ratio of 1:1.4, then heating and stirring at 60°C for 8 hours, preparing a viscous liquid under the autocatalysis of amino groups, and then vacuum drying at 60°C.
[0054] Furthermore, the mass ratio of the hyperbranched siloxane methanol solution to the hydroxypropyl methylcellulose composite sol is 1:1-2; and the mass ratio of the hyperbranched siloxane to the zirconium tungstate core layer in the flame retardant for coating is 2:1.
[0055] Comparative Example 1
[0056] The difference between Comparative Example 1 and Example 2 is that only hyperbranched siloxane and hydroxypropyl methylcellulose composite sol are used to compound the flame retardant for coating, and the remaining steps and ingredients are the same as those in Example 2.
[0057] Comparative Example 2
[0058] The difference between Comparative Example 2 and Example 2 is that the flame retardant shell layer is prepared by using hydroxypropyl methylcellulose composite sol; the remaining steps and ingredients are the same as those in Example 2.
[0059] Comparative Example 3
[0060] The difference between Comparative Example 3 and Example 2 is that the flame retardant shell layer is prepared by using hyperbranched siloxane, and the other steps and components are the same as those in Example 2.
[0061] Comparative Example 4
[0062] The difference between Comparative Example 4 and Example 2 is that only hyperbranched siloxane composite graphene oxide is used to prepare the flame retardant shell layer; the remaining steps and components are the same as those in Example 2.
[0063] Effect example
[0064] The flame retardant for coating prepared in the example and the comparative example was added to the waterborne polyurethane coating, mixed at a mass ratio of 1:5, and stirred at a speed of 200 rpm for 30 minutes to obtain a flame retardant coating.
[0065] The flame retardant coating and the blank coating waterborne polyurethane were formed into films on glass sheets, dried at room temperature and placed in an oven at 40°C for 3 days. The tensile strength and elongation at break of the flame retardant coating were tested according to the national standard GB / T528-2009; dumbbell test length type I: 25.0±0.5mm, tensile machine moving speed: 500mm / min.
[0066] Table 1 below shows the test and analysis results of various properties of flame retardant coatings prepared using the flame retardants for coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 5 of the present invention.
[0067] Table 1
[0068]
[0069]
[0070] From Table 1, it can be found that the flame retardants for coatings prepared in Examples 1 to 3 have good flame retardancy and good compatibility with coatings, and can effectively avoid the problem of cracking of the coating coating at high temperatures due to the use of flame retardants; Compared with Comparative Example 1, Example 2 finds that the flame retardant for coatings uses zirconium tungstate as the core layer, which not only increases the hardness of the flame retardant, but also effectively avoids the problem of cracking of the coating coating at high temperatures due to the use of flame retardants; Compared with Comparative Examples 2, 3, and 4, Example 2 finds that hyperbranched siloxane and hydroxypropyl methylcellulose composite sol are composited to prepare a flame retardant shell layer, wherein the hydroxypropyl methylcellulose composite sol is obtained by combining chitosan, hydroxypropyl methylcellulose, guar gum, and graphene oxide, and the prepared flame retardant for coatings has good hardness, good flame retardancy, and good compatibility with coatings.
[0071] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A flame retardant for coatings, the structure of the flame retardant for coatings is a core-shell structure, characterized in that: The core-shell structure comprises a zirconium tungstate core layer and a flame retardant shell layer from the inside to the outside; the flame retardant shell layer is obtained by compounding a hyperbranched siloxane and a hydroxypropyl methylcellulose composite sol; the hyperbranched siloxane is obtained by a mixed reaction of N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water; the hydroxypropyl methylcellulose composite sol is obtained by sequentially adding acetic acid to chitosan, hydroxypropyl methylcellulose and guar gum and then adding graphene oxide to mix.
2. The flame retardant for coating according to claim 1, characterized in that: The zirconium tungstate core layer is obtained by sequentially mixing a zirconium source, a tungsten source and deionized water, and then sequentially adding a flocculant and an acid solution, and performing reflux, standing, filtering, washing, drying, grinding and heat treatment.
3. A method for preparing a flame retardant for coatings as claimed in any one of claims 1 to 2, characterized in that: The method comprises the following preparation steps: (1) zirconium oxynitrate and deionized water are mixed in a mass ratio of 1:2-6, stirred and dissolved at a speed of 200-300 rpm, and then a tungsten source is added and stirred for 30-60 minutes to obtain a primary mixed solution. At this time, the molar ratio of tetravalent zirconium ions and hexavalent tungsten ions contained in the primary mixed solution is 1:
2. Then, 0.01-0.02 mass of polyvinyl pyrrolidone of zirconium oxynitrate is added and stirred for 10 hours. A 68% nitric acid solution is added to obtain a secondary mixed solution. The mass fraction of nitric acid in the secondary solution is 3-15%. Then, reflux for 48 hours and stand for 21 days. After filtering, washing, drying, grinding through a 100-200 mesh sieve, and heat treating at 610°C for 5 hours, a zirconium tungstate core layer is obtained. (2) The zirconium tungstate core layer obtained in step (1) is ultrasonically dispersed in methanol with a volume of 30 to 50 times its mass for 20 to 40 minutes to obtain a zirconium tungstate core layer suspension; a mixture of hydroxypropyl methylcellulose composite sol and a methanol solution of hyperbranched siloxane is then added dropwise to the zirconium tungstate core layer suspension, and the mixture is continuously stirred at a speed of 1200 to 1600 rpm during the addition process. After the addition is completed, the mixture is continuously stirred overnight, and then filtered, and rinsed with deionized water and ethanol repeatedly for 2 to 4 times, and then vacuum freeze-dried to obtain a flame retardant for coatings.
4. The method for preparing a flame retardant for coatings according to claim 3, characterized in that: The tungsten source includes ammonium tungstate.
5. The method for preparing a flame retardant for coatings according to claim 3, characterized in that: The preparation method of the hydroxypropyl methylcellulose composite sol is as follows: chitosan, hydroxypropyl methylcellulose and guar gum are sequentially added to a 5wt% acetic acid solution and stirred for 30 minutes, and then a 2mg / L graphene oxide solution is added and swelled at 60°C for 3-4 hours to obtain a hydroxypropyl methylcellulose composite sol.
6. The method for preparing a flame retardant for coatings according to claim 5, characterized in that: The hydroxypropyl methylcellulose composite sol contains 0.75 wt % chitosan, 2.5 wt % hydroxypropyl methylcellulose, 0.1-0.2 wt % guar gum, 0.2-0.4 wt % graphene oxide, and 0.5 wt % acetic acid.
7. The method for preparing a flame retardant for coatings according to claim 3, characterized in that: The methanol solution of the hyperbranched siloxane is obtained by dissolving the hyperbranched siloxane in a methanol solution 8 to 10 times its mass; the hyperbranched siloxane is obtained by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane and deionized water in a molar ratio of 1:1.2 to 1.4, then heating and stirring at 60°C for 8 hours, preparing a viscous liquid under the autocatalysis of amino groups, and then vacuum drying at 60°C.
8. The method for preparing a flame retardant for coatings according to claim 3, characterized in that: The mass ratio of the hyperbranched siloxane methanol solution to the hydroxypropyl methylcellulose composite sol is 1:1-2; the mass ratio of the hyperbranched siloxane to the zirconium tungstate core layer in the flame retardant for coating is 1-2:1.
Citation Information
Patent Citations
Swelling flame retardant and preparation method thereof
CN103073725A
Hyperbranched polysiloxane coated ammonium polyphosphate flame retardant and preparation method thereof
CN110606990A